PENGARUH PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT ISS INDONESIA AREA GELORA BUNG KARNO DI JAKARTA SELATAN - Risa Triaudini; Rima Handayani (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Every human resource requires training and discipline in working. Both of these aim to improve employee performance so that they can work optimally. This study aims to examine the effect of job training and work discipline on employee performance at PT. ISS Indonesia Gelora Bung Karno Area, South Jakarta. By using quantitative research methods and a research sample of 64 employees, the results of the study indicate that job training (X1) and work discipline (X2) have a positive and significant influence on employee performance (Y) at PT.ISS Indonesia Gelora Bung Karno Area, In South Jakarta. The constant (a) value of 0.906 states that when job training and work discipline do not increase or do not increase, Employee Performance (Y) remains at 0.906. The coefficient of determination R Square value of 0.838 states that the variables of job training and work discipline contribute 83.8% to the Employee Performance variable (Y) while the rest comes from other variables not discussed. In the F-test, the significance value of the job training and work discipline variables was 0.01 < 0.05, thus rejecting H0 and accepting H1, indicating a positive effect.